Early life allergen‐induced mucus overproduction requires augmented neural stimulation of pulmonary neuroendocrine cell secretion. Issue 9 (19th September 2017) - Barrios, Juliana; Patel, Kruti R.; Aven, Linh; Achey, Rebecca; Minns, Martin S.; Lee, Yoonjoo; Trinkaus‐Randall, Vickery E.; Ai, Xingbin
ABSTRACT: Pulmonary neuroendocrine cells (PNECs) are the only innervated airway epithelial cells. To what extent neural innervation regulates PNEC secretion and function is unknown. Here, we discover that neurotrophin 4 (NT4) plays an essential role in mucus overproduction after early life allergen exposure by orchestrating PNEC innervation and secretion of GABA. We found that PNECs were the only cellular source of GABA in airways. In addition, PNECs expressed NT4 as a target‐derived mechanism underlying PNEC innervation during development. Early life allergen exposure elevated the level of NT4 and caused PNEC hyperinnervation and nodose neuron hyperactivity. Associated with aberrant PNEC innervation, the authors discovered that GABA hypersecretion was required for the induction of mucin Muc5ac expression. In contrast, NT4 −/− mice were protected from allergen‐induced mucus overproduction and changes along the nerve–PNEC axis without any defects in inflammation. Last, GABA installation restored mucus overproduction in NT4 −/− mice after early life allergen exposure. Together, our findings provide the first evidence for NT4‐dependent neural regulation of PNEC secretion of GABA in a neonatal disease model. Targeting the nerve–PNEC axis may be a valid treatment strategy for mucus overproduction in airway diseases, such as childhood asthma.—Barrios, J., Patel, K. R., Aven, L., Achey, R., Minns, M. S., Lee, Y., Trinkaus‐Randall, V. E., Ai, X. Early life allergen‐induced mucus overproduction requires augmented neural stimulation of pulmonary neuroendocrine cell secretion. FASEB J. 31, 4117–4128 (2017). www.fasebj.org —Barrios, Juliana, Patel, Kruti R., Aven, Linh, Achey, Rebecca, Minns, Martin S., Lee, Yoonjoo, Trinkaus‐Randall, Vickery E., Ai, Xingbin Early life allergen‐induced mucus overproduction requires augmented neural stimulation of pulmonary neuroendocrine cell secretion. FASEB J. 31, 4117–4128 (2017)